Why emerging supply chain technologies initially disappoint: Blockchain, IoT, and AI. Issue 6 (7th March 2022) - Sodhi, ManMohan S.; Seyedghorban, Zahra; Tahernejad, Hossein; Samson, Danny
Abstract: In this paper, we explore why users' experiences with emerging supply chain technologies comprise inflated expectations followed by disappointment in the early stages of adoption, as per the Gartner Hype Cycle. We used "affordance theory" to study how managers perceive emerging technologies to explain their adoption experience. Affordance theory indicates that perceived benefits—and goals and constraints—depend on the interaction between technology and the users, not on the technology alone. First, we used the literature for two purposes: first, to obtain characteristics of blockchain, Internet of Things (IoT), and artificial intelligence (AI) as emerging technologies; and second, to itemize generic goals, affordances, and constraints in adopting any supply chain technology. Next, we asked 400+ supply chain managers to select those affordances, constraints, and goals that they viewed as pertinent to their organizations' supply chains for whichever of these three technologies they were implementing. Finally, we compared the responses across technologies for individual respondents (who selected more than one technology) and within the pool of respondents. We found that respondents who selected more than one technology made distinct selections individually for the different technologies relevant to them. The pooled responses across all respondents, however, prioritized the aggregated goals, affordances, and constraints in the same way, regardless of the technology, the organization, or the network features of the supply chain. Overall, it appears that the characteristics of the technology do not inform user expectations at the early stages of adoption. This initial disconnect—between characteristics and expectation—may explain the "inflated expectations" followed by the early "trough of disappointment" with emerging technologies in the Gartner Hype Cycle, as users focus on obtaining the same benefits for the supply chain from any new emerging technology. Only subsequent shared experiences can lead to the long "slope of enlightenment."